2015
DOI: 10.5539/ijel.v5n3p120
|View full text |Cite
|
Sign up to set email alerts
|

Prepositional Errors in the Writings of Pakistani ESL Students

Abstract: Today, English has emerged as an important means of communication across the world including Pakistan. In Pakistan, it enjoys the status of second language as it is offered as a compulsory subject from primary level up to higher classes. In addition, there is great need and demand for having a sound grasp over English language to encounter professional challenges. However, Pakistani learners still face various problems while speaking and writing English. This study examined the abuse of English prepositions by… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
3
0

Year Published

2016
2016
2019
2019

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 9 publications
(4 reference statements)
2
3
0
Order By: Relevance
“…Hence, the given hypothesis proved that female ESL learners committed more errors. The present study corroborate with Abdul Saeed (2015) findings of preposition, whereas he says students find difficulties in the use of preposition of place and direction and his study also shows that female learners committed more errors as compare to male.…”
Section: Resultssupporting
confidence: 90%
See 3 more Smart Citations
“…Hence, the given hypothesis proved that female ESL learners committed more errors. The present study corroborate with Abdul Saeed (2015) findings of preposition, whereas he says students find difficulties in the use of preposition of place and direction and his study also shows that female learners committed more errors as compare to male.…”
Section: Resultssupporting
confidence: 90%
“…The students did not have enough knowledge about these types of prepositions. As Abdul Saeed (2015) found the same findings in his study on prepositional errors in the writings of Pakistani ESL learners. He found that students faced most difficulty in the use of place, direction and time preposition.…”
Section: Resultssupporting
confidence: 71%
See 2 more Smart Citations
“…(xiii) I went to the trip *in (on) 3 rd December 2000. (xiv) *At (on) that day, I was very ill. One possible explanation for the above errors is the L1 interference in the target language (see also [20]). Malay students may have been influenced by the use of the Malay preposition 'pada'.…”
Section: Wrong Selection Of 'On' (Preposition Of Time)mentioning
confidence: 99%